Prototipo de vivienda progresiva para las comunidades indígenas de la Amazonia colombiana - Ramos Borja, Jayber Ernesto (Universidad Antonio Nariño, 2024)
This research is intended to be carried out from the perspective of habitat and housing transformations in an indigenous community located in the municipality of Puerto Leguizamo Putumayo, Muruy ethnic group; with the purpose of knowing how are the ways of inhabiting these communities in relation to the ecosystem environment in which it is related and produced, taking into account components such as production, how they appropriate and how they transform the territory, practices that have generated the need to build a domestic habitation as a result of their rush to have a place to live, thus allowing the development of construction systems that are linked to the term vernacular housing, as an immediate response to their needs and as an articulation of housing with respect to its forms to produce and appropriate their habitat. Carrying out an analysis that allows us to know more about the relationship of the domestic habitat with the ecosystem and how your home adapts to the transformation of its environment, its ways of inhabiting and producing, allowing a relationship of how it is the sustainable development of the ecosystem and housing. Responding to the proposal of a housing prototype for the community, which bets on a progressive, incremental and flexible pattern, depending on the ways of living and the articulation of ecosystem services and production of the community, betting on the sustainability, without abandoning their culture and tradition.